How Pesantren Economic Restriction Policy Enhances Institutional Sustainability - Chaerudin; Dailibas; Kristanti Rahman; Afiq Chamim Mubaroq; Bramantyo Suryo Nugroho (UPY Business and Management Journal (UMBJ), 2026)
Purpose: This article aims to critically examine the implementation of the protectionist economic model in the context of pesantren financial management. This model refers to the internal policies of pesantren in limiting the entry of goods or services from outside the pesantren environment, with the hope of strengthening economic independence and financial efficiency. Methodology: This research uses a qualitative approach with a case study method in several pesantren that have implemented protectionist policies for more than three years. Findings: The main findings explain that the success of financial management in pesantren is reflected in the ability to apply the principles of efficiency, accountability, and transparency in the management of their economy. The implementation of these principles is realized through an organized organizational structure, an institutional culture that supports good governance, and visionary leadership focused on strengthening financial independence. Additionally, the study shows that although the protectionist policy successfully reduced financial leaks and improved internal control, there are implementation challenges in the form of resistance from students and limitations in internal production capacity. Implications: This article contributes to the literature on financial management community based educational institutions and offers practical recommendations for other pesantren that wish to implement similar policies. Originality: This study integrates a modern financial management perspective with traditional Islamic economic value in the context of community-based educational institutions such as pesantren. Previous research has focused more on defining the protective economy in pesantren, the business unit created, and focusing on a single pesantren.